Model analizy portfelowej z kosztami transakcyjnymi - Wrzosek, Piotr (Model of portfolio analysis with transaction costs, 2006)
The paper presents extended version of Markowitz model. Unlike classical model presented solution lets take into account transaction costs. This lets avoid selecting overly diversified portfolios, witch are ineffective because of high transaction costs (mainly provisions) associated with buying and selling them. The paper also includes a practical example of presented model use based on data from Warsaw Stock Exchange.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 592-604